Pengaruh Leader-Member Exchange, Perceived Organizational Support, Person-Job Fit, Dan Person-Organizational Fit Terhadap Kinerja Pegawai Dinas Perpustakaan Dan Arsip Daerah, Yogyakarta: Indonesia - Saputra, Dymas Warih Nugraha; Kurniawan, Ignatius Soni; Septyarini, Epsilandri (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2024)
This research intends to examine the influence of leader-member exchange (LMX), perceived organizational support (POS), person-job fit (PJF), and person-organizational fit (POF) on employee performance. The study used the population coverage of all employees of the Dinas Perpustakaan dan Arsip Daerah (DPAD) Yogyakarta. Data were collected using a questionnaire on 46 employees by census. Following a traditional assumption test, the analysis used multiple linear regression analysis. The results stated that LMX, PJF, and POF had no significant effect on employee performance. The test also revealed that POS has a significant impact on employee performance. Implications are made by providing organizational support to stimulate employee performance.